Passive and active environmental controls : Informing the schematic designing of buildings - Heerwagen, Dean (New York, NY McGraw-Hill, 2004)
The book serves as an introduction to the subject of environmental controls and presents information necessary for the schematic design of buildings. It describes the various components of a particular system, developing how a system functions, how the systems components fit together and how spaces are organized to accommodate these components. The book demonstrates how each system is integrated with other building systems, such as the structural systems and the overall architecture of the building.
Includes index
Keywords: Kỹ thuật công trình xây dựng